Insights on the health benefits of the bioactive compounds of coffee silverskin extract. (August 2016) - Fernandez-Gomez, Beatriz; Lezama, Adriana; Amigo-Benavent, Miryam; Ullate, Mónica; Herrero, Miguel; Martín, María Ángeles; Mesa, Maria Dolores; del Castillo, Maria Dolores
Highlights: Total phenolic and chlorogenic acids decrease by changes of pH during digestion. Phytochemicals composing coffee silverskin were metabolised in the body. Phytochemicals' metabolism may start in the gastrointestinal tract due to pH change. Coffee silverskin extract may protect pancreas and reduce diabetes' risk. Phytochemicals and their metabolites may contribute to the bioactivity of the extract. Abstract: The bioaccessibility of chlorogenic acid (CGA) and caffeine in coffee silverskin extracts (CSE) and the contribution of these substances to the prophylactic effect of CSE on the pathogenesis of diabetes have not been reported. This study aimed to evaluate the bioaccessibility, bioavailability and bioactivity of CGA and caffeine alone and in CSE in the pancreas of rats treated with streptozotocin–nicotinamide (type 2 diabetes model). Metabolism of CGA and caffeine started in the gastrointestinal tract due to changes of pH taking place during digestion. Their metabolites protected pancreatic cells against the risk of diabetes. This is the first in vivo study to demonstrate a specific chemo-protective effect of CSE in pancreatic tissue, and this effect may be associated with its antioxidant capacity. Daily administration of CSE, CGA or caffeine 35 d previous to the induction of diabetes significantly reduced (p < 0.05) pancreatic oxidative stress and protein damage.